PERSONAL DEVELOPMENT OF EMPLOYEES OF PJSC "KHMELNYTSKA MASLOSYRBAZA": RESEARCH OF PROVISION POSSIBILITIES AND SEARCH FOR DIRECTIONS FOR IMPROVEMENT - FEDORYSHYNA, Larysa; UMEROVA, Kateryna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The relevance of the topic of the article is due to the fact that the personal development of personnel forms an internal resource for adapting to changes, increasing innovation and strengthening the competitive position of the enterprise. The purpose of the article is to substantiate the need to ensure the personal development of each employee of the enterprise, to study the state of this process in PJSC "Khmelnytska Maslosyrbaza" and to search for directions for its improvement. It is substantiated that the development of the employee’s personality includes not only improving qualifications, but also the formation of motivation, emotional intelligence, creative skills and critical thinking, the ability to self-study and adapt to changes. We believe that personally developed employees are able not only to effectively perform current tasks, but also to act as agents of change, generators of ideas, initiators of innovative processes. They demonstrate a high level of involvement, are able to quickly respond to environmental challenges, and also contribute to the formation of a positive climate in the team. Accordingly, the development of the employee’s personality has not only individual, but also strategic value for the enterprise. The results of a survey of employees of PJSC "Khmelnytska Maslosyrbaza" on the current state and opportunities for personal development at the enterprise are presented. It was found that employees believe that there are no clear conditions for professional growth, and also feel little support from management in resolving issues related to development; most of them also believe that the enterprise has almost no conditions for personal development and professional growth. The exchange of experience takes place informally, without organized events. Employees express a desire to receive greater opportunities for development, in particular, through internal trainings and seminars, a flexible schedule for combining work with study, as well as career development programs. The most common answers are the desire to participate in professional development programs, depending on the format and topic of training. Recommendations for improving the personnel development process at the enterprise under study are formulated, their advantages and risks of implementation are outlined. Among the recommendations are the organization of internal training courses and trainings, the introduction of a blended learning format (online and offline), the launch of a mentoring program at the enterprise, the organization of rotation between divisions of the enterprise, the launch of an internal educational platform, etc.